Optimizing extended ablation margins in papillary thyroid carcinoma using digital pathology - Zhao, Han-xiao; Niu, Yun; Zhao, Zhen-long; Liu, Yu-tong; Yu, Ming-an (Frontiers in Endocrinology, 2025)
BackgroundTo reduce the risk of local recurrence of papillary thyroid carcinoma (PTC) after thermal ablation, in clinical practice, the ablation area is typically extended 2–3 mm beyond the original tumor margin. However, there is no definitive evidence to support the validity of this extended margin.ObjectiveThe objective of this study was to measure the distance from the edge of a PTC to the farthest point of tumor infiltration using digital pathology and to analyze the associated risk factors.MethodsA total of 227 patients who underwent surgical resection for PTC were included in the study. The median age was 45 years. The slides with the maximum tumor diameter were selected as the target slides. Two authors independently assessed the characteristics of the PTCs and measured infiltration distances, with the greatest distance recorded as the infiltration distance. Risk factors associated with infiltration distance were analyzed using the rank-sum test, correlation analysis, and multiple linear regression.ResultsOf the 227 tumors, 23 tumors showed no signs of infiltration; the remaining 204 tumors had infiltration distances ranging from 0.14 to 2.26 mm, with 3 tumors having distances greater than 2 mm (2.17, 2.19 and 2.26 mm). Significant differences in infiltration distances were observed in relation to maximum tumor diameter, lymph node metastases, and tumor growth patterns (TGPs) on the basis of the rank-sum test or correlation analyses. However, multiple linear regression analyses revealed that only TGPs were risk factors for infiltration distance.ConclusionTo minimize the risk of local recurrence of PTC following thermal ablation, extending the ablation margin by 2.5 mm is recommended, regardless of the tumor stage.